The radioluminescence investigation of lead sodium borate doped with Sm3+ glass scintillator. (March 2022) - Limkitjaroenporn, P.; Sangwaranatee, N.; Yonphan, S.; Borisut, P.; Kothan, S.; Wongdamnern, N.; Kim, H.J.; Kaewkhao, J.
Abstract: The effects of Sm 3+ -doped lead sodium borate glasses in compositions of (79-x)B2 O3 : 20Na2 O: xPbO: 1Sm2 O3 with x = 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 and 55 mol% were studied by using the melt-quenching technique. The glass samples were characterized the spectroscopic properties. From the photoluminescence, the emission spectra of glasses showed 4 peaks bands at 563( 4 G5/2 → 6 H5/2 ), 599( 4 G5/2 → 6 H7/2 ), 645( 4 G5/2 → 6 H9/2 ), and 706( 4 G5/2 → 6 H11/2 ) nm. The maximum intensity was identified at 10 mol% of PbO. Similarly, the radioluminescence spectra (RL) of the glasses were found in 4 emission bands, The strongest emission peak of RL was 597 nm at 5 mol% of PbO. The maximum intensity of PL and RL shows the difference in PbO content due to the difference in interaction mechanisms of host material and activator from UV and X-ray excitation. The absorption spectra revealed the highest emission wavelength at 599 nm. The color coordinate in CIE-1931 was found to locate in the orange region. Highlights: Glass scintillator from lead sodium borate doped with Sm 3+ were developed. Physics, optical and luminescence properties were studied. Integral scintillation efficiency of glass is 5.9% of BGO crystal. Lead sodium borate doped with Sm 3+ show good emission for scintillator.